2011
DOI: 10.15835/nbha3927183
|View full text |Cite
|
Sign up to set email alerts
|

Toxicity of Some Cinnamic Acid Derivatives to Common Bean (Phaseolus vulgaris)

Abstract: Cinnamic acid derivatives are an important class of biologically active compounds, playing an important role in the plants' development, but may also present a wide range of actions: antimicrobial, antioxidant, antiinflamatory, antitumoral. The present study investigated the toxicity of ten cinnamic acid derivatives on Phaseolus vulgaris, this being the first step in evaluating their pharmacotoxicological potential (usually, plant toxicity tests are used for ecotoxicity assessment, but they can also provide so… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
22
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(24 citation statements)
references
References 15 publications
2
22
0
Order By: Relevance
“…Indeed, t-cinnamic acid showed lowest ED 50 value (Table 1), compared to p-coumaric, caffeic, ferulic acids, which are characterized by the presence of substitutions in the aromatic ring. These results are in agreement with previous works, which reported that the presence of substitutions in the aromatic ring changed the allelopathic activity (Yu and Matsui 1997;Abenavoli et al 2010;Jitãreanu et al 2013). Furthermore, Wong et al (2005) demonstrated that also the position and/or the isomerization of the substitution group defined the chemicals allelopathic activity.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Indeed, t-cinnamic acid showed lowest ED 50 value (Table 1), compared to p-coumaric, caffeic, ferulic acids, which are characterized by the presence of substitutions in the aromatic ring. These results are in agreement with previous works, which reported that the presence of substitutions in the aromatic ring changed the allelopathic activity (Yu and Matsui 1997;Abenavoli et al 2010;Jitãreanu et al 2013). Furthermore, Wong et al (2005) demonstrated that also the position and/or the isomerization of the substitution group defined the chemicals allelopathic activity.…”
Section: Discussionsupporting
confidence: 93%
“…Moreover, the number and lateral root length are strongly dependent on the plant hormone auxin, which plays a central role in organ development and elongation, in shoot/root branching and plastic growth responses (Zažímalová et al 2010), in lateral root initiation (Casimiro et al 2003;De Smet et al 2006), primordia development (Benková et al 2003) and emergence (Laskowski et al 2006). Furthermore, t-cinnamic acid is a potent auxin inhibitor (Jitãreanu et al 2013) as are other cinnamic acid derivatives, and these could interfere with auxin transport and/or distribution, reducing the lateral root number.…”
Section: Discussionmentioning
confidence: 99%
“…The toxicity tests were conducted in Petri dishes. 40 bean seeds per dish were placed on an artificial substrate (Whatman® no.1 circles of filter paper), impregnated with different dilutions of the tested substances, following the procedure presented in our previous work (A. JITAREANU & al [4]). Three active concentrations were tested for each substance (concentration A -28.6 μg cm -2 ; concentration B -57.3 μg cm -2 ; concentration C -114.6 μg cm -2 ).…”
Section: The Phaseolus Toxicity Testmentioning
confidence: 99%
“…Taking into consideration the fact that toxicity assessment is of great importance for pharmaceutical substances, we considered necesary to subject the biologically active substances to a phytobiological screening, in order to evaluate their influence on living organisms. For this, we investigated the effects of some nonbrominated cinnamic acid derivatives on Phaseolus vulgaris, observing the inhibitory effect of the tested compounds (A. JITAREANU & al [4]).…”
Section: Introductionmentioning
confidence: 99%
“…The ferulic, m-cumaric, p-cumaric, vanilic acids presented strong inhibitory effect on the germination in E. crus-galii, and the cinnamic acid strongly inhibited root and stem elongation in the same species . Also, the derivatives of the cinnamic acid affected the formation of radicular hairs and induced modifications in the structure of the vascular system in beans (Jitareanu et al, 2013).…”
Section: Mean Value±sementioning
confidence: 99%